p53-dependent regulation of Mcl-1 contributes to synergistic cell death by ionizing radiation and the Bcl-2/Bcl-XL inhibitor ABT-737 - Tagscherer, Katrin; Faßl, Anne; Sinkovic, Tabea; Combs, Stephanie; Roth, Wilfried (Apoptosis, 2012)
Treatment with the Bcl-2/Bcl-XL inhibitor ABT-737 is a promising novel strategy to therapeutically induce apoptotic cell death in malignant tumors such as glioblastomas. Although many studies have demonstrated that ABT-737 acts synergistically with chemotherapeutic drugs, the possibility of a combined treatment with ionizing radiation (IR) and ABT-737 has not yet been thoroughly investigated. Similarly, the relationship between p53 function and the pro-apoptotic effects of ABT-737 are still obscure. Here, we demonstrate that IR and ABT-737 synergistically induce apoptosis in glioblastoma cells. The sensitivity to ABT-737-mediated cell death is significantly increased by the IR-dependent accumulation of cells in the G2/M cell cycle phase. Wild type p53 function inhibits the efficacy of a combined IR and ABT-737 treatment via a p21-dependent G1 cell cycle arrest. Moreover, mutant as well as wild type p53 counteract the pro-apoptotic activity of ABT-737 by maintaining the expression levels of the Mcl-1 protein. Thus, p53 regulates the sensitivity to ABT-737 of glioblastoma cells. Our results warrant a further evaluation of a novel combination therapy using IR and ABT-737. The efficacy of such a therapy could be substantially enhanced by Mcl-1-lowering strategies.